2002
DOI: 10.1128/iai.70.10.5721-5729.2002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Murine Model ofUreaplasma urealyticumPneumonia

Abstract: Ureaplasma urealyticum respiratory tract colonization in preterm infants has been associated with a high incidence of pneumonia and the development of bronchopulmonary dysplasia. However, study of this human pathogen has been hampered by the absence of animal models. We have developed the first juvenile mouse model of Ureaplasma pneumonia and characterized the histopathology during the month following inoculation. C3H/ HeN mice were inoculated intratracheally with a mouse-adapted clinical Ureaplasma isolate (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 49 publications
6
32
0
Order By: Relevance
“…Coalson's group has previously noted an increase in alveolar macrophages in a baboon model of prematurity and infection with U. urealyticum (20). Our data are also compatible with those reported in a murine model of U. urealyticum infection in which an initial airway neutrophilia was followed by increased airway macrophages (21). Studies of postmortem lungs by Viscardi's group showed that alveolar macrophages predominated when the infants were colonized with U. Urealyticum but with airway neutrophilia when they were not (22).…”
Section: Discussionsupporting
confidence: 82%
“…Coalson's group has previously noted an increase in alveolar macrophages in a baboon model of prematurity and infection with U. urealyticum (20). Our data are also compatible with those reported in a murine model of U. urealyticum infection in which an initial airway neutrophilia was followed by increased airway macrophages (21). Studies of postmortem lungs by Viscardi's group showed that alveolar macrophages predominated when the infants were colonized with U. Urealyticum but with airway neutrophilia when they were not (22).…”
Section: Discussionsupporting
confidence: 82%
“…Studies show that colonization of the reproductive tract is commonly associated with infertility, abortions, premature births and lung injury in neonates (Ruhnke et al 1984, Murray 1991, Buzinhani et al 2011. In other mycoplasma species, such as U. urealyticum, was observed that the presence of bacteria in the respiratory tract of infants stimulates an increasing total number of white blood cells (Viscardi et al 2002). However, the observed leukocytosis is associated with low immunity (Tegtmeier et al 1999, Ohlsson et al 1993, Honma et al 2007).…”
Section: Discussionmentioning
confidence: 92%
“…Ultra-structural changes were observed with reduction of microvilli in the endometrial epithelial cells (McGowin et al 2013). However, for Ureaplasma ssp., histological alterations are mostly related to chronic fetal infections (Robinson et al 2013) or other body sites as lung (Viscardi et al 2002). Although this study did not assess the progression of later periods, this model of infection by U. diversum does not induce an acute infl ammatory response in healthy animals.…”
Section: Discussionmentioning
confidence: 95%
“…The mice were anesthetized with intraperitoneal xylazine and ketamine solution inoculum (ketamine 100 mg/kg; xylazine 12 mg/kg). Then we performed the intratracheal inoculum of 50µL of the bacterial solution or sterile saline as adapted from Viscardi (Viscardi et al, 2002). 24 hours after challenge, the animals were euthanized by overdosage of ketamine and xylazine.…”
Section: Intratracheal Challenge and Euthanasiamentioning
confidence: 99%